Participatory Action in Optimizing the Operational Curriculum of Educational Units containing the Profile of Pancasila and Rahmatan lil Alamin - Faizah, Silviana Nur; Dina, Lia Nur Atiqoh Bela; Khairiyah, Ummu (LP2M INSURI Ponorogo, 2024)
The essential need for character education development in the Operational Curriculum of Educational Units (KOSP) at SDN 3 Pagentan and SDN 2 Wonorejo is evident. However, the existing KOSP documents, initially adapted from another school due to a lack of knowledge in KOSP development, do not fully align with the characteristics and needs of the school community. This service empowers teachers in both schools to enhance their understanding of KOSP and develop documents enriched with the Strengthening Project for the Profile of Pancasila-Rahmatan lil Alamin Students (P5-RA), considering each school's unique characteristics and needs. Using a participatory action research (PAR) approach, the service involves problem identification, analysis, action preparation, program socialisation, implementation, and monitoring and evaluation. The instruments include tests and assessment rubrics, revealing a significant improvement in teachers' knowledge of KOSP, with scores increasing from 71 to 80 in the moderate category. The service activities also produce a grand design of character integrated into KOSP documents enriched with P5-RA, developed by teachers in both schools based on their unique characteristics and needs. In summary, this service positively impacts teachers' knowledge and optimises the availability of KOSP documents enriched with P5-RA as guidelines for strengthening character education in schools.